A class of chiral thermally activated delayed fluorescent polymers and their applications

By synthesizing chiral TADF polymers based on binaphthyl derivatives and benzophenone as the light-emitting layer or dopant of white circularly polarized organic light-emitting diodes, the problems of high cost and racemization risk in the existing technology are solved, and efficient white light emission and high device efficiency are achieved.

CN118909173BActive Publication Date: 2025-09-26CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410944189.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-09-26
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Existing white circularly polarized organic light-emitting diodes (CP-WOLEDs) rely on double-layer devices, which have high manufacturing costs and the risk of racemization, making it difficult to achieve efficient single white light emission.

Method used

A chiral green TADF polymer was synthesized by adjusting the ratio of TADF units using binaphthyl derivatives as chiral sources, benzophenone as electron acceptor, and acridine as electron donor. The chiral green TADF polymer was used as the light-emitting layer or dopant to prepare white circularly polarized organic light-emitting diodes using solution processing.

Benefits of technology

White circularly polarized organic light-emitting diodes with high external quantum efficiency and high color rendering index are achieved, which reduces manufacturing costs, avoids the risk of racemization, and improves device efficiency and luminescence performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909173B_ABST
    Figure CN118909173B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of organic electroluminescent materials, and specifically discloses a class of chiral thermally activated delayed fluorescence polymers and their applications. Using binaphthyl derivatives as chiral sources, benzophenone as electron acceptors, and acridine as electron donors, binaphthyl is introduced into TADF units and suspended on polystyrene skeleton side chains. A series of chiral green light TADF polymers are synthesized by adjusting the ratio of TADF units during polymerization using a non-conjugated polymerization strategy. The polymer can detect obvious circularly polarized luminescence signals in both the ground state and the excited state. Using the polymer as an acceptor, a red electroexciton complex is formed with 1,1-bis[(di-4-toluamino)phenyl]cyclohexane to construct a white circularly polarized light-emitting diode. The TADF polymer improves exciton utilization by reverse intersystem crossing, and provides an effective chiral source for the electroexciton complex system, which is of great significance for constructing a new axial chirality TADF polymer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic electroluminescent materials, and specifically discloses a class of chiral thermally activated delayed fluorescent polymers and applications thereof. Background Art

[0002] In recent years, circularly polarized luminescent materials have shown broad application prospects in the fields of optical data storage, chiral sensing, bio-responsive imaging, asymmetric synthesis and chiral materials. In addition to the application of circularly polarized photoluminescence, the development of circularly polarized electroluminescence (CPEL) has also attracted widespread attention and is considered to be more valuable in optoelectronic technology. Since Meijer et al. first reported circularly polarized polymer light-emitting diodes (CP-PLEDs) in 1997, CPEL of CP-PLEDs has developed rapidly. However, due to the theoretical internal quantum efficiency (IQE) of 25%, traditional fluorescent polymer materials cannot achieve satisfactory performance in CP-PLED devices. In order to achieve more efficient CPEL, chiral phosphorescent complexes with a theoretical IQE of 100% are used as the light-emitting materials of the corresponding devices. However, phosphorescent materials still face problems such as high cost, environmental issues and instability of coordination bonds.

[0003] As the third generation of luminescent materials, thermally activated delayed fluorescence (TADF) materials with pure organic molecular structures can achieve the same 100% theoretical IQE as phosphorescent materials and are considered to be promising pure organic materials for manufacturing organic light-emitting diodes (OLEDs). Unlike traditional fluorescent emission materials, TADF materials always have a sufficiently small singlet-triplet energy gap (ΔE) due to the sufficient separation of the distribution of the highest occupied molecular orbitals (HOMOs) and the lowest unoccupied molecular orbitals (LUMOs). ST ), which is less than 0.3 eV. Therefore, triplet excitons can be fully utilized through the reverse intersystem crossing (RISC) process without the need for additional energy supply, thereby improving the exciton utilization rate.

[0004] As a new type of solid-state light source, white organic light-emitting diodes (WOLEDs) have shown broad application prospects in the lighting field. With high external quantum efficiency (EQE) and high color rendering index (CRI), WOLEDs offer advantages such as excellent color rendering and a long lifespan, making them a research focus in academia and industry.

[0005] In order to achieve efficient white light emission, it is necessary to simultaneously include a certain proportion of the three primary colors (blue, green, and red) or two complementary colors (blue with orange or yellow) in the emission layer. In this regard, various strategies have been used to obtain white light emission, such as physically mixing monochromatic luminescent materials into host polymer materials, or chemically tethering luminescent materials to polymer chains. Compared with chiral small molecules, chiral polymers are easier to achieve single white light emission by controlling the ratio of different emission colors during polymerization. In 2022, Cheng Yixiang's research group copolymerized a binaphthyl derivative unit with three blue, green, and red luminescent units to design a class of chiral white light polymers S- / R-WP1 and S- / R-WP2. The standard white CP-OLED based on S- / R-WP2 has a CRI of up to 95 at the International Commission on Illumination (CIE) coordinates (0.33, 0.34). In the wavelength range of 425 to 760 nm, the maximum brightness (L max ) is approximately 3000cd m -2 , electroluminescence asymmetry factor (g EL ) is 10 -3 , but its EQE max Only 0.54%.

[0006] Exciplexes are molecular charge transfer excited-state luminescent materials composed of an electron donor and an electron acceptor. Compared to single-molecule luminescent materials containing both donor and acceptor molecules, exciplexes exhibit larger Stokes shifts and broader emission peaks, facilitating the construction of white-light OLEDs. Furthermore, novel exciplex systems with TADF properties can achieve high exciton utilization through efficient upconversion of triplet excitons, improving device efficiency. Furthermore, they possess a lower energy gap, thereby reducing device driving voltage. Therefore, combining the advantages of exciplexes in achieving white-light emission and high exciton utilization is of great significance for the construction of efficient white circularly polarized organic light-emitting diodes based on them.

[0007] Most of the white circularly polarized organic light-emitting diodes reported so far rely on double-layer devices. As an alternative approach, there is a growing demand for CP-WOLEDs that place different chiral luminescent materials in a single emitting layer. Recently, Chen Chuanfeng's group realized CP-WOLEDs based on the strategy of integrating conformational isomerization donors and chiral acceptors in a single molecule. Unfortunately, this CP-WOLED needs to be realized through a vacuum evaporation process, which has harsh conditions, high manufacturing costs, and the potential risk of racemization. Therefore, it is of great significance to continue to propose new construction strategies to achieve efficient electro-induced circularly polarized single white light emission. Summary of the Invention

[0008] In order to further reduce ΔE ST, in order to obtain more efficient TADF materials. The present invention uses binaphthyl derivatives as chiral sources, benzophenone as electron acceptor, and acridine as electron donor, and directly introduces the binaphthyl chiral source into the TADF unit, suspending it on the side chain of the polystyrene skeleton. By adjusting the ratio of TADF units during polymerization, a series of chiral green light TADF polymers (R)-E-0.02 / (S)-E-0.02, (R)-E-0.05 / (S)-E-0.05 and (R)-E-0.1 / (S)-E-0.1 are designed and synthesized. By optimizing the ratio of chiral TADF units in the polymer, the polymer (R)-E-0.1 / (S)-E-0.1 can detect obvious circularly polarized luminescence signals in both the ground state and the excited state. The binaphthyl chiral source can effectively induce the circularly polarized luminescence of the polymer. In the scheme, benzophenone is an electron acceptor and acridine is an electron donor. The combination of the two is conducive to the separation of the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) of the TADF unit in the polymer, which is beneficial to reducing the energy gap difference between single and triplet states and improving the luminescence efficiency of the material.

[0009] The present invention first synthesizes a new type of axially chiral TADF polymer material with a binaphthyl derivative as a chiral source, benzophenone as an electron acceptor, and acridine as an electron donor. This type of material has the following structure:

[0010]

[0011] The present invention also provides a method for preparing a chiral thermally activated delayed fluorescent polymer, using a binaphthyl derivative as a chiral source, benzophenone as an electron acceptor, and acridine as an electron donor. The binaphthyl chiral source is directly introduced into the TADF unit and suspended on the side chain of the polystyrene skeleton. By adjusting the ratio of the TADF units during polymerization, a series of chiral green thermally activated delayed fluorescent polymers are synthesized using a non-conjugated polymerization strategy, the ratio of the chiral TADF monomers during polymerization is optimized, and the structure-activity relationship of the material is systematically studied.

[0012] The binaphthyl derivative is (R / S)-binaphthol, which has the advantages of cross-stable spatial configuration, strong chiral induction ability, and low price.

[0013] The proportion of chiral TADF units is 2%-10%.

[0014] The present invention also provides the application of a new axially chiral TADF polymer material as a light-emitting layer material for a white circularly polarized organic light-emitting diode. By using a solution processing method, a chiral thermally activated delayed fluorescence polymer material is used as a light-emitting layer or a light-emitting layer dopant to prepare the light-emitting layer of a white circularly polarized organic light-emitting diode, thereby obtaining a white circularly polarized organic light-emitting device with excellent light-emitting performance.

[0015] The mass percentage of the chiral luminescent material as a dopant in the luminescent layer is 50-90 wt %.

[0016] The external quantum efficiency of a white circularly polarized organic light-emitting diode prepared by using a chiral thermally activated delayed fluorescent polymer material as a light-emitting layer or a light-emitting layer dopant is 10.8-15.1%.

[0017] The present invention has the following technical advantages:

[0018] 1. Using benzophenone as electron acceptor and acridine as electron donor, the combination of the two is conducive to the separation of the highest occupied molecular orbital (HOMO) and the lowest occupied molecular orbital (LUMO) of the polymer, which is beneficial to reducing ΔE ST , it is easy to obtain TADF materials and can improve the luminescence efficiency of the materials; the thermally activated delayed fluorescent material is non-conjugated with the binaphthyl chiral source. The non-conjugated polymer backbone has a high triplet energy, which can reduce unnecessary energy loss from the TADF unit to the polymer backbone. Based on this polymerization method, a series of new axial chiral TADF polymer luminescent materials are constructed; by optimizing the ratio of chiral TADF units in the polymer, it is given enhanced circularly polarized luminescence properties while maintaining the photophysical properties of the TADF unit;

[0019] 2. Based on the synthesized chiral TADF polymer as the acceptor and the commercial achiral TAPC as the donor, the light-emitting layer dopant was constructed, and a high-efficiency solution-processed electroexcimer complex white light device was obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0020]

Figure 1

[0021] Gel permeation chromatography curves of (R) / (S)-E-0.05 and (R) / (S)-E-0.1.

[0022]

Figure 2

[0023] Thermogravimetric loss curves of (R) / (S)-E-0.05 and (R) / (S)-E-0.1.

[0024]

Figure 3

[0025] Cyclic voltammetry curves of (R) / (S)-E-0.05 and (R) / (S)-E-0.1.

[0026]

Figure 4

[0027]

Figure 5

[0028]

Figure 6

[0029]

Figure 7

[0030]

Figure 8

[0031]

Figure 9

[0032]

Figure 10

[0033]

Figure 11

[0034]

Figure 12

[0035]

Figure 13

[0036]

Figure 14

[0037]

Figure 15

[0038]

Figure 16

[0039]

Figure 17

[0040]

Figure 18

[0041]

Figure 19

[0042]

Figure 20

[0043] The following specific implementation cases are intended to further illustrate the present invention, but these specific implementation cases do not limit the scope of protection of the present invention in any way.

[0044] Example 1 Chiral TADF Polymer Synthesis:

[0045]

[0046] Synthesis of compound 1

[0047] To a 100 mL single-necked flask were added the following raw materials: p-bromobenzophenone (3.0 g, 11.5 mmol), 9,10-dihydro-9,9-dimethylacridine (3.6 g, 17.3 mmol), sodium tert-butoxide (3.3 g, 34.5 mmol), tri-tert-butylphosphine tetrafluoroborate (334.0 mg, 1.2 mmol), palladium acetate (232.0 mg, 1.0 mmol), and 50.0 mL of toluene. Under nitrogen protection, the reaction was allowed to proceed at 90°C for 18 h. The reaction solution was cooled to room temperature, the solvent was removed by rotary evaporation, and the product was extracted three times with DCM, washed three times with water, and dried over anhydrous magnesium sulfate. The filtrate was filtered and the solvent was again evaporated. The product was separated by column chromatography using PE and DCM as eluents (volume ratio 4:1) to obtain 4.4 g of a yellow solid in a 98% yield. 1 H NMR (400MHz, CD2Cl2) δ (ppm) 8.00-7.96 (m, 2H), 7.83-7.80 (m, 2H), 7.57 (ddd, J = 6.8, 4.0, 1.3Hz, 1H), 7.48 (tt ,J=6.7,1.2Hz,2H),7.41(dd,J=6.3,4.4Hz,4H),6.94-6.84(m,4H),6.26(dd,J=8.0,1.4Hz,2H),1.60(s,6H). 13 C NMR (101MHz, CDCl3) δ (ppm) 152.78, 151.72, 132.30, 131.65, 130.65, 130.14, 128. 27,127.05,126.22,125.86,125.04,121.86,83.98,25.23,24.67.TOF-MS(ESI)m / z calcd for C 28 H 23NO:390.08;[M+H]+found:389.18.

[0048] Synthesis of compound 2

[0049] Compound 1 (850.0 mg, 2.2 mmol) and 30.0 mL of anhydrous chloroform were added to a 100 mL single-necked flask. N-bromosuccinimide (971.0 mg, 5.5 mmol) dissolved in 20.0 mL of anhydrous chloroform was added dropwise at 0°C. The mixture was then allowed to react in the dark at room temperature for 12 h. After completion of the reaction, the solvent was evaporated, and the crude product was precipitated with DCM and MeOH. Filtering afforded 1.1 g of a yellow solid in a 91% yield. 1 H NMR (400MHz, CDCl3) δ (ppm) 8.08 (d, J = 7.6Hz, 2H), 7.90 (d, J = 7.4Hz, 2H), 7.65 (t, J = 7.1Hz, 1H), 7. 58-7.50 (m, 4H), 7.43 (d, J=7.6Hz, 2H), 7.09 (d, J=8.6Hz, 2H), 6.18 (d, J=8.6Hz, 2H), 1.65 (s, 6H). 13 C NMR (101MHz, CDCl3) δ (ppm) 195.72, 144.30, 139.33, 137.73, 137.07, 132.97, 1 31.96, 130.89, 130.14, 129.45, 128.58, 128.27, 115.92, 113.85, 36.37, 30.92. TOF-MS(ESI)m / z calcd for C 28 H 21 Br2NO[M+H]+:546.01; found:548.11.

[0050] Synthesis of compound 3

[0051] To a 200 mL single-necked flask were added (R / S)-binaphthol (5.0 g, 17.5 mmol), 1,4-dibromo-2,3-difluorobenzene (5.2 g, 19.2 mmol), cesium carbonate (11.4 g, 35.0 mmol), and 100.0 mL of anhydrous DMF. The mixture was heated to 120°C under nitrogen (N2) and reacted overnight. The reaction solution was cooled to room temperature, the solvent was removed by rotary evaporation, and the product was extracted three times with dichloromethane (DCM), washed three times with water, and dried over anhydrous magnesium sulfate. The filtrate was filtered and the solvent was again evaporated. The product was separated by column chromatography using petroleum ether (PE) and DCM (volume ratio 7:1) as eluents to obtain 4.3 g of a white solid with a yield of 47%. 1H NMR (400MHz, CDCl3) δ (ppm) 8.00 (d, J = 8.8Hz, 2H), 7.95 (d, J = 8.2Hz, 2H), 7.60-7.55 (m, 4H), 7.50 (t, J = 7.4Hz, 2H), 7.39 (t, J = 7.5Hz, 2H), 7.27 (s, 2H). 13 C NMR (101MHz, CDCl3) δ (ppm) 150.49, 147.73, 132.07, 132.03, 130.98, 128.65, 128.46, 126.94, 126.85, 125.79, 125.46, 121.20, 115.70.

[0052] Synthesis of compound 4

[0053] Phenylboronic acid (117.6 mg, 0.96 mmol), compound 3 (1.0 g, 1.9 mmol), sodium carbonate (2.0 g, 19.3 mmol), tetrakistriphenylphosphine palladium (111.5 mg, 0.096 mmol), 30.0 mL of tetrahydrofuran, and 15.0 mL of water were added to a 100 mL single-necked flask. The mixture was heated to 80°C under nitrogen for 24 h. The reaction solution was cooled to room temperature, the solvent was removed by rotary evaporation, and the product was extracted three times with dichloromethane (DCM), washed three times with water, and dried over anhydrous magnesium sulfate. The filtrate was filtered and the solvent was dried again. The product was separated by column chromatography using PE and DCM (volume ratio 8:1) as eluents to obtain 305.0 mg of a white solid with a yield of 31%. 1 H NMR (400MHz, CD2Cl2) δ (ppm) 7.99 (d, J = 8.8Hz, 1H), 7.95-7.91 (m, 1H), 7.83 (d, J = 8.2Hz, 1H), 7.77 (d, J=8.8Hz,1H),7.59(d,J=8.8Hz,1H),7.47-7.27(m,12H),7.02(d,J=8.4Hz,1H),6.84(d,J=8.8Hz,1H). 13 C NMR (101MHz, CDCl3) δ (ppm) 150.93, 150.85, 147.24, 147.17, 136.84, 135.36, 132.04, 131.98, 131.90, 131.63, 130.66, 130.56, 129.69 ,128.42,128.29,128.17,127.99,127.60,126.83,126.73,126.63,126.16,125.73,125.48,125.42,125.37,121.53,120.94,115.25.

[0054] Synthesis of compound 5

[0055] To a 50 mL single-necked flask were added compound 4 (0.3 g, 0.58 mmol), pinacol diboron (177.4 mg, 0.698 mmol), potassium acetate (285.6 mg, 2.9 mmol), [1,1'-bis(diphenylphosphino)ferrocene]palladium dichloride (21.3 mg, 0.029 mmol), and 25.0 mL of analytically pure toluene solution. The mixture was heated to 110°C under N2 protection for 24 h. The reaction solution was cooled to room temperature, the toluene was removed by rotary evaporation, and the reaction mixture was extracted three times with DCM, washed three times with water, dried over anhydrous magnesium sulfate, and filtered. The filtrate was collected, the solvent was again evaporated, and vacuum dried and used directly in the next reaction.

[0056] Synthesis of compound 6

[0057] Compound 2 (250.0 mg, 0.5 mmol), compound 5 (183.0 mg, 0.2 mmol), sodium carbonate (484.0 mg, 4.6 mmol), tetrakistriphenylphosphine palladium (26.4 mg, 0.00002 mmol), 15.0 mL of tetrahydrofuran, and 7.5 mL of water were added sequentially to a 50 mL single-necked bottle. The mixture was heated to 80 ° C under N2 protection and reacted for 24 h. The reaction solution was cooled to room temperature, the solvent was removed by rotary evaporation, extracted three times with DCM, washed three times with water, dried over anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was dried again and separated by column chromatography using PE and DCM (volume ratio 4:1) as eluents to obtain 73.0 mg of a yellow solid with a yield of 18%. 1 H NMR (400MHz, CD2Cl2) δ (ppm) 7.95 (d, J = 8.4Hz, 2H), 7.85 (t, J = 9.0Hz, 3H), 7.80-7.77 (m, 3H) ,7.65(d,J=2.0Hz,1H),7.58-7.49(m,4H),7.47-7.38(m,8H),7.37-7.33(m,2H),7.28(dd,J =12.4,5.2Hz,3H),7.22-7.16(m,3H),7.08(d,J=8.8Hz,1H),7.02(dt,J=8.8,2.6Hz,1H),6. 93(d,J=8.8Hz,1H),6.27(d,J=8.6Hz,1H),6.15(d,J=8.8Hz,1H),1.66(s,3H),1.60(s,3H). 13C NMR (101MHz, CDCl3) δ (ppm) 195.74, 151.45, 151.36, 146.98, 146.85, 144.57, 139.51, 139.28, 137.65, 137.46, 13 7.10,134.45,134.34,132.79,132.75,132.47,132.04,131.56,131.51,131.01,130.57,130.29,130.06,129.82, 129.49,129.21,128.46,128.35,128.32,128.29,128.09,127.27,126.75,126.70,126.44,126.39,125.78,125.7 5,125.41,125.20,125.16,125.11,121.30,115.80,113.87,113.46,36.35,31.42,31.22,26.89.TOF-MS(ESI)m / z calcd for C 60 H 40 BrNO3:901.22;[M+H]+found:902.33.

[0058] Synthesis of compound 7

[0059] Compound 6 (165.0 mg, 0.2 mmol), vinylboronic acid pinacol ester (42.0 mg, 0.3 mmol), sodium hydroxide (73.0 mg, 1.8 mmol), tetrakistriphenylphosphine palladium (11.0 mg, 0.009 mmol), 15.0 mL of tetrahydrofuran, and 7.5 mL of water were added sequentially to a 50 mL single-necked flask. The mixture was heated to 80° C. under N2 protection and reacted for 24 h. The reaction solution was cooled to room temperature, the solvent was removed by rotary evaporation, and then extracted three times with DCM, washed three times with water, dried over anhydrous magnesium sulfate, filtered, and the filtrate was collected. The solvent was again dried by rotary evaporation, and the product was separated by column chromatography using PE and DCM (volume ratio 3:1) as eluents to obtain 100.0 mg of a yellow solid with a yield of 65%. 1HNMR (400MHz, CD2Cl2) δ (ppm) 7.95 (d, J = 8.5Hz, 2H), 7.84 (t, J = 8.7Hz, 3H), 7.81-7.76 (m, 3H), 7.68 (d, J = 2.0Hz, 1H) ,7.58-7.49(m,3H),7.43(dd,J=15.3,7.9Hz,8H),7.36(dd,J=14.4,7.3Hz,3H),7.28(t,J=7.4Hz,3H),7.19(q,J=8.1 Hz,3H),7.09(d,J=8.8Hz,1H),7.01(dd,J=8.6,1.9Hz,1H),6.93(d,J=8.8Hz,1H),6.60(dd,J=17.6,10.9Hz,1H),6.2 7(d,J=8.6Hz,1H),6.21(d,J=8.5Hz,1H),5.54(dd,J=17.6,0.7Hz,1H),5.05-5.00(m,1H),1.69(s,3H),1.63(s,3H). 13 C NMR (101MHz, CDCl3) δ (ppm) 195.91, 151.57, 151.46, 147.06, 146.93, 145.01, 140.05, 139.48, 137.77, 137.34, 137.27, 136.53, 134.5 7,134.42,132.82,132.74,132.12,131.63,131.58,131.15,130.71,130.38,130.35,130.14,130.02,129.91,128.51,128.40,128.36 ,128.28,128.16,127.32,126.91,126.84,126.48,126.45,125.84,125.47,125.28,125.21,125.17,124.35,123.86,121.40,114.42 ,113.89,111.17,36.28,34.72,34.59,31.83,31.66,31.55,29.12,26.97,25.34,22.87,22.73,20.77,14.21,11.52.TOF-MS(ESI)m / z calcd for C 62 H 43 NO3:849.32;[M+H]+found:850.52.

[0060] Synthesis of polymer (R)-E-0.02 / (S)-E-0.02

[0061] A series of chiral green-emitting TADF polymers were synthesized by introducing binaphthyl into the TADF unit, with the chiral TADF unit suspended on the side chains of the polystyrene backbone at a feed ratio of 2%. The specific experimental method is as follows: Compound 7 (17.0 mg, 0.02 mmol), styrene (102.1 mg, 0.98 mmol), azobisisobutyronitrile (0.6 mg, 0.004 mmol), and 0.6 mL of anhydrous tetrahydrofuran were added sequentially to a 25 mL Schlenk flask. The mixture was first cryogenically deoxygenated (77 K), then nitrogen was introduced. This operation was repeated three times, and finally, under nitrogen protection, it was heated to 55°C for 48 hours. After cooling to room temperature, the mixture was precipitated with acetone to remove the monomer and initiator, filtered, and the resulting residue was completely dissolved in tetrahydrofuran. Methanol was then added dropwise to precipitate the residue, and a yellow solid was obtained by suction filtration. (R)-E-0.02 was 59.6 mg, (S)-E-0.02 was 65.8 mg, and the yields were 5% and 5%, respectively. 1 The H NMR spectrum shows a chemical shift of 7.8-8.0 ppm for the hydrogen peak in the TADF unit, and 5.8-8.0 ppm for the hydrogen peak in the benzene ring region and styrene. The integral ratio of these two regions can be used to determine the actual TADF unit content in the polymer. The molar TADF unit contents corresponding to (R)-E-0.02 / (S)-E-0.02 are 2.3% and 2.3%, respectively, which closely match the feed ratio.

[0062] Synthesis of polymer (R)-E-0.05 / (S)-E-0.05

[0063] A series of chiral green-emitting TADF polymers were synthesized by introducing binaphthyl into the TADF unit, with the chiral TADF unit suspended on the side chains of the polystyrene backbone at a feed ratio of 5%. The specific experimental method is as follows: Compound 7 (42.5 mg, 0.05 mmol), styrene (98.9 mg, 0.95 mmol), azobisisobutyronitrile (0.6 mg, 0.004 mmol), and 0.7 mL of anhydrous tetrahydrofuran were added sequentially to a 25 mL Schlenk flask. The mixture was first cryogenically deoxygenated (77 K), then nitrogen was introduced. This operation was repeated three times, and finally, under nitrogen protection, it was heated to 55°C for 48 hours. After cooling to room temperature, the mixture was precipitated with acetone to remove the monomer and initiator, filtered, and the resulting residue was completely dissolved in tetrahydrofuran. Methanol was then added dropwise to precipitate the residue, and a yellow solid was obtained by suction filtration. The polymers (R)-E-0.05 and (S)-E-0.05 weighed 119.6 mg and 109.7 mg, respectively, with yields of 5% and 8%, respectively. Similarly, the actual TADF unit content in the polymers can be determined based on the integral ratio of the two regions. The molar TADF unit contents corresponding to (R)-E-0.05 / (S)-E-0.05 are 5.0% and 5.1%, respectively, which are very close to their feed ratios.

[0064] Synthesis of polymer (R)-E-0.1 / (S)-E-0.1

[0065] A series of chiral green-emitting TADF polymers were synthesized by introducing binaphthyl into the TADF unit, with the chiral TADF unit suspended on the side chains of the polystyrene backbone at a feed ratio of 10%. The specific experimental method is as follows: Compound 7 (85.0 mg, 0.10 mmol), styrene (93.7 mg, 0.90 mmol), azobisisobutyronitrile (0.6 mg, 0.004 mmol), and 0.9 mL of anhydrous tetrahydrofuran were added sequentially to a 25 mL Schlenk flask. The mixture was first cryogenically deoxygenated (77 K), then nitrogen was introduced. This operation was repeated three times, and finally, under nitrogen protection, it was heated to 55°C for 48 hours. After cooling to room temperature, the mixture was precipitated with acetone to remove the monomer and initiator, filtered, and the resulting residue was completely dissolved in tetrahydrofuran. Methanol was then added dropwise to precipitate the residue, and a yellow solid was obtained by suction filtration. The polymers (R)-E-0.1 and (S)-E-0.1 weighed 106.5 mg and 95.7 mg, respectively, with yields of 11% and 8%, respectively. Similarly, the actual TADF unit content in the polymers can be determined based on the integral ratio of the two regions. The molar TADF unit contents corresponding to (R)-E-0.1 / (S)-E-0.1 are 10.2% and 10.2%, respectively, which is very close to their feed ratio.

[0066] Example 2

[0067] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 were subjected to gel permeation chromatography using THF as the eluent to determine their molecular weight and PDI. Figure 1 It can be seen that the weight average molecular weight of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 ranges from 11700 to 62600 Da / mol, and the PDI ranges from 1.20 to 1.96.

[0068] Example 3

[0069] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 were heated in the range of 30-600°C at a rate of 20°C per minute under N2, and the thermogravimetric curves were measured. Figure 2 It can be seen that the temperatures at which polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 decompose by 5% are 381 / 389°C, 380 / 384°C and 395 / 389°C, respectively.

[0070] Example 4

[0071] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 were dissolved in acetonitrile solution (10 -5 mol / L) to study its redox characteristics. Figure 3 It can be seen that irreversible oxidation potentials are observed in the range of 0.99 eV to 1.10 eV for polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05, and (R) / (S)-E-0.1, while no reduction potentials are detected in the range of 0 to 2.0 V. Calculated according to the formula, the HOMO energy levels of (R / S)-E-0.02 are –5.35 / –5.32 eV, (R / S)-E-0.05 are –5.34 / –5.31 eV, and (R / S)-E-0.1 are –5.25 / –5.24 eV. The LUMO energy levels are -2.61 / –2.58 eV, -2.60 / –2.57 eV, and -2.51 / –2.50 eV, respectively. Clearly, the HOMO and LUMO energy levels increase with increasing proportions of chiral TADF units.

[0072] Example 5

[0073] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 were dissolved in toluene to prepare 10 -5 M solution, and test its UV-visible absorption and photoluminescence spectrum. Figure 4 (a) It can be seen that the UV-visible absorption spectra of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in solution have roughly two absorption peaks: the absorption peak at short wavelength (310-350nm) is mainly attributed to the π-π* transition absorption of the material; the absorption peak at long wavelength (400-450nm) is attributed to the charge transfer (ICT) transition absorption peak from the donor unit to the acceptor unit in the polymer. Figure 4 As shown in (a), the maximum emission peaks of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 are approximately 510 nm, which is in the green light region. Figure 4 (b) is the photoluminescence spectra of all polymers in pure films. The maximum emission peak of the polymers is in the range of 512-521 nm, which is in the green light region.

[0074] Example 6

[0075] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 were prepared to the same concentration (10 -5 M) in different proportions of tetrahydrofuran and water solvents, and tested its emission spectrum to study its aggregation-induced emission enhancement characteristics. Figure 5 As can be seen, the emission intensity of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05, and (R) / (S)-E-0.1 first decreases and then gradually increases as the water content increases. The dot-line plot of the emission intensity versus water content clearly shows that the polymers aggregate as the water content increases, confirming the AIEE properties of this series of polymers.

[0076] Example 7

[0077] The pure films of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 were placed in a low-temperature test kettle. After evacuation for 15 minutes, liquid nitrogen was slowly added until the temperature dropped to 77K. The fluorescence and phosphorescence spectra were tested using a flash xenon lamp with an excitation wavelength of 350nm. Figure 6 It can be seen that the ΔE of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 is calculated according to the formulaST The range is 0.16eV-0.19eV, all less than 0.30eV, indicating that it should have TADF properties.

[0078] Example 8

[0079] The fluorescence lifetimes of the polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 in pure films were tested under nitrogen atmosphere. Figure 7 As shown, the fitting results show that the instantaneous lifetimes of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 are in the nanosecond level, which are 16.0 / 16.5ns, 17.9 / 16.5ns and 28.0 / 24.6ns, respectively.

[0080] Example 9

[0081] The transient fluorescence spectra of the polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 were tested in a pure film under a nitrogen atmosphere. Figure 8 As shown, at room temperature, all polymers have distinct instantaneous and delayed lifetimes. The delayed lifetimes of all polymers exhibit a biexponential decay in the microsecond range, being 14.3μs / 13.1μs, 8.8μs / 11.1μs, and 3.0μs / 4.0μs, respectively, indicating that all polymers possess TADF properties.

[0082] Example 10

[0083] The transient fluorescence spectra of the polymer (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 pure films prepared in Example 1 were tested at 100, 200 and 300 K in a nitrogen atmosphere. Figure 9 As shown, it can be seen that as the temperature increases, the delayed component increases successively, which fully confirms the TADF characteristics of the polymer.

[0084] Example 11

[0085] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 were dissolved in toluene to prepare 10 -5 M solution, and tested its circular dichroism (CD) absorption and CPL spectrum in pure film state to study its circularly polarized luminescence properties. Figure 10It can be seen that the CD absorption spectra of all polymers show perfect mirror symmetry, indicating that they have chirality in the ground state; however, no obvious chiral signals were detected in the CPL spectra of the pure films of polymers (R) / (S)-E-0.02 and (R) / (S)-E-0.05.

[0086] Example 12

[0087] The polymer (R) / (S)-E-0.1 prepared in Example 1 was dissolved in dichloromethane to prepare 10 -5 M solution, and tested its circular dichroism (CD) absorption and CPL spectrum in pure film state to study its circularly polarized luminescence properties. Figure 11 It can be seen that the CD absorption spectrum of polymer (R) / (S)-E-0.1 shows perfect mirror symmetry, indicating that it has chirality in the ground state; with the increase of the proportion of chiral TADF units, the CPL spectrum of polymer (R) / (S)-E-0.1, which is close to mirror symmetry, reflects the chiral luminescence characteristics of the excited state, and the chiral signal is significantly enhanced. lum -2.8×10 -3 and +2.6×10 -3 .

[0088] Example 13

[0089] The polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 are used in organic electroluminescent devices. Non-doped OLED devices were prepared by solution processing using the polymer as the device light-emitting layer. The device structure is: ITO / PEDOT:PSS (35nm) /

[0090] (R / S)-E-0.02 / (R / S)-E-0.05 / (R / S)-E-0.1(35nm) / TmPyPB(55nm) / LiF(1nm) / Al

[0091] (120nm). Figure 12 It can be seen that due to the good energy level matching of the device structure, the device achieves a low turn-on voltage. At the same time, an EQE of the polymer (R / S)-E of 0.02 was observed. max EQE of polymer (R / S)-E-0.05 is 7.6 / 7.8%; max 5.9 / 6.6%; EQE of polymer (R / S)-E-0.1 max It is 6.1 / 4.0%.

[0092] Example 14

[0093] Application of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 in organic electroluminescent devices. Based on the polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 as chiral acceptors, commercial TAPC (manufacturer: Luminescence Technology Corp. (Lumtec); purity: Sublimed>99.5%) as achiral donor, a doping device was prepared with a doping ratio of 7:3. The device structure was: ITO / PEDOT:PSS(35nm) / (R / S)-Ex(x=0.02, 0.05 and 0.1):TAPC(7:3)(35nm) / TmPyPB(55nm) / LiF(1nm) / Al(120nm). Figure 13 It can be seen that in addition to the device's intrinsic emission peak (R / S)-E-0.1 at approximately 520nm, a new orange-red emission peak appears at approximately 580nm. The combined effect of these two peaks enables white light emission. The electroluminescence spectrum of the doped device shows an orange-red emission peak at approximately 580nm as the voltage increases to approximately 5.6V. The emission intensity of this orange-red emission peak gradually increases with increasing voltage.

[0094] Example 15

[0095] The photoluminescence spectra of the polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 were tested in pure films and 70wt% doped TAPC films to further prove the origin of the orange-red emission peak. Figure 14 The PL spectra of the polymer films before and after TAPC doping are essentially similar, with only a slight blue shift observed after doping. This is likely due to the weakening of intermolecular interactions within the polymer (R / S)-E-0.1 after TAPC doping. The newly formed peak in the EL spectrum is not observed in the PL spectrum of the donor and acceptor blend film, which is consistent with the definition of an electroexciton complex and confirms the origin of the white light emission.

[0096] Example 16

[0097] Application of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 in organic electroluminescent devices. Based on the polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 prepared in Example 1 as chiral acceptors and commercial TAPC as achiral donor, doped devices were prepared with doping ratios of 5:5, 7:3 and 9:1. The device structure was: ITO / PEDOT:PSS (35nm) / (R / S)-Ex (x=0.02, 0.05 and 0.1):TAPC (5:5, 7:3 and 9:1) (35nm) / TmPyPB (55nm) / LiF (1nm) / Al (120nm). Figure 15 It can be seen that white light emission is achieved due to the formation of orange-red electroexciton complexes between the polymer and TAPC in the light-emitting layer. When the doping ratio of polymer (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 to TAPC is 5:5, the EQE of the device prepared based on (R / S)-E-0.02:TAPC as the light-emitting layer is max 11.0 / 10.6%; (R / S)-E-0.05: TAPC's EQE max 6.7 / 6.8%; (R / S)-E-0.1: TAPC's EQE max When the doping ratio of polymer (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 to TAPC is 7:3, the EQE of the device prepared based on (R / S)-E-0.02:TAPC as the light-emitting layer is 9.7 / 4.3%. max 13.6 / 16.2%; (R / S)-E-0.05: TAPC's EQE max 8.0 / 8.2%; (R / S)-E-0.1: TAPC's EQE max When the doping ratio of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 to TAPC is 9:1, the EQE of the device prepared based on (R / S)-E-0.02:TAPC as the light-emitting layer is max 9.2 / 14.4%; (R / S)-E-0.05: TAPC's EQE max 6.4 / 7.0%; (R / S)-E-0.1: EQE of TAPC maxThe device achieved the maximum external quantum efficiency when the polymer doping ratio of (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 and TAPC was 7:3.

[0098] Example 17

[0099] Based on the polymer (R) / (S)-E-0.1 prepared in Example 1 as a chiral acceptor and commercial TAPC as an achiral donor, a white electroexcimer complex device was prepared with an acceptor and donor optimal device efficiency doping ratio of 7:3 to study its circularly polarized electroluminescence performance. Figure 16 It can be seen that the broad and mirror-symmetrical electro-induced circularly polarized luminescence spectrum of the device reflects its circularly polarized electroluminescence characteristics. (R) / (S)-E-0.1:|g of TAPC EL -1.0×10 -3 and +1.0×10 -3 .

[0100] Example 18

[0101] The polymer (R) / (S)-E-0.170 wt% prepared in Example 1 was doped into TAPC to prepare a doped film and its CPL spectrum was tested to study its circularly polarized luminescence properties. Figure 17 It can be seen that the CPL spectrum of (R) / (S)-E-0.1:TAPC is close to mirror symmetry, which reflects the circularly polarized luminescence characteristics. lum -2.4×10 -3 and +2.0×10 -3 .

[0102] Example 19

[0103] Application of polymers (R) / (S)-E-0.02, (R) / (S)-E-0.05 and (R) / (S)-E-0.1 in Example 1 in organic electroluminescent devices. Based on the electroexcimer complex formed by the polymer (R) / (S)-E-0.1 and TAPC prepared in Example 1 as the guest, CBP as the host of the white light photoexcimer complex, and doping devices with a host and guest doping ratio of 5:5, 3:7 and 1:9 respectively. The device structure is: ITO / PEDOT:PSS(35nm) / CBP:((R / S)-E-0.1:TAPC(7:3))(5:5, 3:7 and 1:9)(35nm) / TmPyPB(55nm) / LiF(1nm) / Al(120nm). Figure 18It can be seen that the device performance is further improved by the effective FRET energy transfer between the host and the guest. When the CBP:((R / S)-E-0.1:TAPC) doping ratio is 5:5, the EQE of the device prepared based on CBP:((R / S)-E-0.1:TAPC) as the light-emitting layer is max When the CBP:((R / S)-E-0.1:TAPC) doping ratio is 3:7, the EQE of the device prepared based on CBP:((R / S)-E-0.1:TAPC) as the light-emitting layer is 13.8 / 14.0%. max When the CBP:((R / S)-E-0.1:TAPC) doping ratio is 1:9, the EQE of the device prepared based on CBP:((R / S)-E-0.1:TAPC) as the light-emitting layer is 13.9 / 15.1%. max The device achieved the maximum external quantum efficiency when the CBP:((R / S)-E-0.1:TAPC) doping ratio was 3:7.

[0104] Example 20

[0105] Based on the electroexcimer complex formed by the polymer (R) / (S)-E-0.1 and TAPC prepared in Example 1 as the guest, CBP as the host of the white light electroexcimer complex, a white electroexcimer complex type device was prepared with the optimal device efficiency doping ratio of host to guest of 3:7 to study its circularly polarized electroluminescence performance. Figure 19 It can be seen that the broad and mirror-symmetrical electro-induced circularly polarized luminescence spectrum of the device reflects its circularly polarized electroluminescence characteristics. EL -1.8×10 -3 and +2.4×10 -3 .

[0106] Example 21

[0107] 70 wt% of the electroexcimer complex formed by the polymer (R) / (S)-E-0.1 and TAPC prepared in Example 1 was doped into CBP to prepare a doped film and its CPL spectrum was tested to study its circularly polarized luminescence properties. Figure 20 It can be seen that the CPL spectrum of CBP: ((R / S)-E-0.1: TAPC) is close to mirror symmetry, which reflects the circularly polarized luminescence characteristics. lum -3.0×10 -3 and +2.4×10 -3 .

[0108] Although the present invention has been described in conjunction with the preferred embodiments, the present invention is not limited to the above embodiments, and it should be understood that the appended claims summarize the scope of the present invention. Under the guidance of the inventive concept, those skilled in the art should appreciate that certain changes made to the various embodiments of the present invention will be covered by the spirit and scope of the claims of the present invention.

Claims

1. A chiral thermally activated delayed fluorescent polymer characterized by: The molecular structure of the chiral thermally activated delayed fluorescent polymer is as follows: 、 or .

2. A method for preparing a chiral thermally activated delayed fluorescent polymer according to claim 1, characterized in that: The preparation method comprises the following steps: using a binaphthyl derivative as a chiral source, benzophenone as an electron acceptor, and acridine as an electron donor, directly introducing the binaphthyl chiral source into a TADF unit, suspending the unit on a polystyrene skeleton side chain, and synthesizing a series of chiral green photothermally activated delayed fluorescent polymers using a non-conjugated polymerization strategy by adjusting the ratio of the TADF units during polymerization.

3. The chiral thermally activated delayed fluorescent polymer according to claim 1, characterized in that The binaphthyl derivative is ( R / S )-binaphthol.

4. A use of the chiral thermally activated delayed fluorescent polymer according to claim 1, characterized in that: The chiral thermally activated delayed fluorescence polymer is used for preparing white circularly polarized organic light-emitting diodes.

5. The use of the chiral thermally activated delayed fluorescent polymer according to claim 4, characterized in that: The light-emitting layer of a white circularly polarized organic light-emitting diode is prepared by a solution processing method using a chiral thermally activated delayed fluorescent polymer as a light-emitting layer or a light-emitting layer dopant.

6. The use of the chiral thermally activated delayed fluorescent polymer according to claim 5, characterized in that: The external quantum efficiency of white circularly polarized organic light-emitting diodes prepared with chiral thermally activated delayed fluorescent polymers as light-emitting layers or light-emitting layer dopants is 10.8-15.1%.

7. The use of the chiral thermally activated delayed fluorescent polymer according to claim 5, wherein Chiral thermally activated delayed fluorescent polymer is used as a dopant in the light-emitting layer to prepare white circularly polarized organic light-emitting diodes with a doping mass percentage of 50-90 wt%.

Citation Information

Patent Citations

  • Near-infrared thermal activation delayed fluorescence luminescent material based on dicyanophenene and application of near-infrared thermal activation delayed fluorescence luminescent material

    CN115490631A

  • High-efficiency chiral liquid crystal fluorescent material and application thereof

    CN115745885A